Question-formatted reproaches in classroom management. Issue 3 (3rd July 2021) - Klattenberg, Revert
ABSTRACT: This paper provides a micro-analytical investigation into the action formation and ascription of interrogatives as reproaches and the interactional exigencies and functions that motivate this reproach design choice for classroom management. It is shown how the participants draw on an interplay of turn-design, epistemic territories and features of sequence organisation to produce these question-formatted reproaches. These can then be used to directly address forms of pupils' conduct as unacceptable, encourage the adherence to behavioural norms, establish the condition for upcoming reproaches and highlight pupils' failure to adhere to behavioural expectations.